The Effectiveness of the Autonomous Learner and Jigsaw Cooperative Learning Models on the Indonesian Language Learning Outcomes of Fourth-Grade Students at SDI Bonerate No. 85: Efektivitas Model Pembelajaran Autonomous Learner dan Kooperatif Tipe Jigsaw terhadap Hasil Belajar Bahasa Indonesia Siswa Kelas IV SDI Bonerate No. 85 - Wihdat Amal; Ira Irviana; Rahma Ashari Hamzah (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2026)
This study aims to examine the effectiveness of integrating the autonomous learner model with the cooperative learning model of the jigsaw type in improving Indonesian language learning outcomes among fourth-grade students at SDI Bonerate No. 85 Kepulauan Selayar. The focus of this research is to determine the extent to which the combined implementation of both models enhances students’ learning outcomes. This study employed a pre-experimental design using a one-group pretest–posttest approach, involving 38 students as participants. Data were collected through tests, observations, and documentation. The results indicate an improvement in the average scores for the autonomous learner model from 38.09 to 52.38, with an N-gain of 0.23 (low category), while the jigsaw model increased from 52.35 to 67.64, with an N-gain of 0.32 (moderate category). The paired sample t-test showed a significance value of < 0.05. Observational findings also revealed increased student independence and collaboration, rising from 41% to 83% and from 69% to 87%, respectively. Thus, the combined models are effective, although the absence of a control group limits the generalizability of the findings.